Linking First Nations data to administrative health data within Manitoba - Ramayanam, Venkata Shravan; Star, Leona (International Journal of Population Data Science, 2018)
Introduction First Nation peoples (FNs) were unable to track their own health care trends due to limitations in datasets. The key linked file enables FNs to identify themselves within administrative datasets and work with Crown governments to bring equity in all services and departments to support FNs understanding of wellness. Objectives and Approach First Nations Health and Social Secretariat of Manitoba (FNHSSM) was established by 2013 resolution of Assembly of Manitoba Chiefs (AMC) and incorporated in 2014. FNHSSM leads and supports research according to FNs criteria approved by the Chiefs in Assembly. Information Sharing Agreements (ISA) have been developed with federal and provincial governments to mandate the processes for data linkage. The ISA allows Indian Status Register (ISR) data of Department of Indigenous Services Canada (DISC) to be transferred to FNHSSM to provide oversight, and link to Provincial Personal Health Information Numbers (PHINs) to create the de-identified, scrambled, and encrypted Key Linked file. Results Previous linkages were done in early 2000s with FNs approval and oversight. The 2018 linkage is the first time that ISAs have been formally developed. ISA-1 is between FNHSSM and Manitoba Health Seniors and Active Living (MHSAL) to create Key Linked file. ISA-2 is between FNHSSM, MHSAL and Manitoba Centre for Health Policy (MCHP) at University of Manitoba, to create the FNs Research File. This research file can only be accessed with application to and approval by the MFNs Health Information Research Governance Committee. This key linked file allows FNHSSM to prepare community health profiles specifically and only for each FN, to respect FNs Data Governance under Chief and Council. A regional report on Manitoba FNs will be created for all MFNs, FNHSSM and MHSAL. Conclusion/Implications Linking datasets helps to strengthen FNs data governance in re-building nations, recognizing FNs inherent right to self-determination. Linking files help to provide meaningful data to advocate for FNs rights and access to the resources and social determinants of health needed to achieve equity in Manitoba.